Location of modulatory β subunits in BK potassium channels - Liu, Guoxia (The Rockefeller University Press, 2010)
Large-conductance voltage- and calcium-activated potassium (BK) channels contain four pore-forming α subunits and four modulatory β subunits. From the extents of disulfide cross-linking in channels on the cell surface between cysteine (Cys) substituted for residues in the first turns in the membrane of the S0 transmembrane (TM) helix, unique to BK α, and of the voltage-sensing domain TM helices S1–S4, we infer that S0 is next to S3 and S4, but not to S1 and S2. Furthermore, of the two β1 TM helices, TM2 is next to S0, and TM1 is next to TM2. Coexpression of α with two substituted Cys’s, one in S0 and one in S2, and β1 also with two substituted Cys’s, one in TM1 and one in TM2, resulted in two αs cross-linked by one β. Thus, each β lies between and can interact with the voltage-sensing domains of two adjacent α subunits.